Case report: risk of skin necrosis related to injectable vancomycin in critically ill newborn infants - Sixtine Gilliot; Mohamed Riadh Boukhris; Morgane Masse; Laurent Storme; Bertrand Décaudin; Pascal Odou; Kevin Le Duc (BMC Pediatrics, 2021)
Abstract Background Vancomycin is commonly used as part of empiric antibiotic therapy in the preterm infants who develop signs and symptoms of infection. Although skin necrosis has been noted to occur following injection of vancomycin into a peripheral vein in an adult patient, this complication has not been previously described in a preterm infant. Case presentation We report the case of a very low birthweight male infant born at 30 weeks gestational age who developed skin necrosis, most likely as a complication of vancomycin administration via a peripheral venous catheter. The immature skin and endothelial cells of this preterm infant may have increased the risk of drugs related venous and skin toxicity. In this case, assumption of a cumulative toxicity with other drugs administered concomitantly via the same catheter can’t be excluded. Conclusions To prevent the risk of skin damage, we advocate that in newborn infants, the administration of vancomycin should be limited to a concentration of < 2.5 mg/mL via a peripheral intravenous catheter if a central venous catheter is not available.